Optimising rabbit performance under cyclic heat stress: effects of nano-chromium chloride on growth, immunity, antioxidant defense, and gene expression in New Zealand White and Rex breeds - Sahar H. El-Nagar; Hisham A. Abdelrahman; Heba A. Basha; Mohamed Atef Helal; Shawky Mahmoud; Youssef A. Attia; Rashed A. Alhotan; S. Leanne Dillard; Heba I. Ghamry; Badriyah S. Alotaibi; Mustafa Shukry (Italian Journal of Animal Science)
Heat stress significantly impairs rabbit productivity, especially in hot climates. This study evaluated the impact of nano-chromium chloride (nano-CrCl3) supplementation on growth performance, antioxidant status, immunity, and gene expression in New Zealand White (NZW) and Rex rabbits under heat stress. A total of 216 rabbits (108 per breed) were used in a 2 × 2 × 3 factorial design: two temperature conditions—comfortable (CT, 24.5 ± 1.3 °C) and cyclic heat stress (CHS, 32.8 ± 1.5 °C)—and three nano-CrCl3 levels (0, 1, and 2 mg/L). Supplementation with 2 mg/L nano-CrCl3 improved body weight gain, feed intake, and feed conversion ratio in both breeds, with NZW rabbits performing better under CHS. Nano-CrCl3 enhanced immunity by increasing phagocytic activity and reducing heterophil-to-lymphocyte ratios, especially under CT. Under CHS, it boosted IgG levels and reduced TNF-α, IL-4, and IFN-γ, indicating an anti-inflammatory effect. Antioxidant activity (SOD and CAT) was higher under CT, while nano-CrCl3 reduced oxidative stress markers such as MDA. Gene expression analysis revealed no direct effect of nano-CrCl3 on HSP70, GHR, or IGF1 expression. However, breed–temperature interactions were significant: NZW rabbits showed HSP70 upregulation under CT and downregulation under CHS; IGF1 was downregulated under CHS in NZW rabbits, while GHR was upregulated in Rex rabbits under the same conditions. In conclusion, nano-CrCl3 at 2 mg/L effectively improved rabbit growth, immunity, and oxidative stress resistance, mitigating the negative effects of heat stress.